Molecular Characterization of Bartonella vinsonii subsp. berkhoffii Genotype III - Cadenas, Maria B. (American Society for Microbiology (ASM), 2008)
The molecular characterization of a Bartonella vinsonii subsp. berkhoffii genotype III strain (NCSU strain 06-CO1) isolated from the blood of a military working dog diagnosed with endocarditis is reported in this study. Several genes were amplified and sequenced for comparative sequence similarity with other strains.